Anatomi Untuk Peningkatan Kualitas Hidup - T. Jacob T. Jacob (Journal of the Medical Sciences (Berkala Ilmu Kedokteran), 1989)
The article describes the various divisions of anatomy made according to the need in facing a particular problem, among others the cla.4ification in functional systems and in levels of the living systems. Since anatomy is determined by both genetics and environment, and the total man also depends on his anatomy, efforts to improve the quality of life necessarily involves improvement in genetic and environmental qualities. The quality of life can thus be studied in terms of the functional anatomical systems and the anatomy at different levels of the living systems.There are many indicators developed to measure the quality of life. Mention is made about demographic indicators, socioeconomic indicators, sociomedical indicators, sociodental indices, biocultural indices and biomedical indices. Indicators based on purely anatomical factors are described, such as body height and weight, growth norms, anthropological measurements, body build and body composition, and biological rhythm.Other approaches could be developed by using vertical and horizontal interrelations of the discipline to study the quality of life from the vantage point of anatomy.Key Words: anatomy – quality of life – health indicators – demographic factors – height-weight indices